2019
DOI: 10.1136/tobaccocontrol-2018-054883
|View full text |Cite
|
Sign up to set email alerts
|

‘The lesser devil you don’t know’: a qualitative study of smokers’ responses to messages communicating comparative risk of electronic and combusted cigarettes

Abstract: IntroductionCommunicating to smokers that e-cigarettes deliver lower levels of harmful chemicals than combusted cigarettes is a challenging issue. This study qualitatively explored smokers’ interpretations of messages communicating the risk of e-cigarettes relative to cigarettes (comparative risk messages).MethodWe developed 12 print comparative risk messages and evaluated them in 12 focus groups with 72 adult smokers (18+ years old) in Atlanta, Georgia.ResultsParticipants interpreted uncertainty about health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
(44 reference statements)
6
19
0
Order By: Relevance
“…In our qualitative study of comparative risk messages, we also observed that the mentioning of specific ingredients in e-cigarettes, including nicotine and formaldehyde, made participants perceive e-cigarettes as very harmful, and they were skeptical that e-cigarettes are less harmful than cigarettes. Additionally, comparative risk messages that compared toxic chemicals in cigarettes and e-cigarettes were consistently viewed as factual [18]. These findings, together with our results showing significant impact of Formaldehyde on the outcomes, suggest the need to communicate about contents of e-cigarettes, including the presence of toxic chemicals such as formaldehyde.…”
Section: Plos Onesupporting
confidence: 61%
“…In our qualitative study of comparative risk messages, we also observed that the mentioning of specific ingredients in e-cigarettes, including nicotine and formaldehyde, made participants perceive e-cigarettes as very harmful, and they were skeptical that e-cigarettes are less harmful than cigarettes. Additionally, comparative risk messages that compared toxic chemicals in cigarettes and e-cigarettes were consistently viewed as factual [18]. These findings, together with our results showing significant impact of Formaldehyde on the outcomes, suggest the need to communicate about contents of e-cigarettes, including the presence of toxic chemicals such as formaldehyde.…”
Section: Plos Onesupporting
confidence: 61%
“…This is important given that harm reduction appears to be conditional on completely switching (and not dual product use) [ 11 ]. However, the limited research on this wording so far is somewhat mixed on whether consumers understand what it means [ 12 , 13 , 14 ]. Camel’s proposed ads also include modified exposure claims (e.g., stating that “scientific studies have shown that Camel Snus contains less of the harmful chemicals than cigarette smoke”) as well as several statements attempting to connect the role of combustion with modified risk and exposure (e.g., “no smoke = less risk”).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative research is important for exploring consumer perceptions and understanding of comparative risk messages and potential variations for developing new ones [ 6 ]. However, limited such investigation exists outside of the industry’s own research [ 12 , 14 , 18 ]. This is important given recommendations for independent MRTP studies outside of the industry [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Correcting misperceptions about SHA without deterring full transition from smoking to ENDS use will require nuanced communications that balance encouragement and uncertainty. Recent findings suggest relative risk messages that compare smoking and vaping may foster more cautious beliefs, though these require testing with more diverse samples 24–26 37…”
Section: Discussionmentioning
confidence: 99%